GPR105-Targeted Therapy Promotes Gout Resolution as a Switch Between NETosis and Apoptosis of Neutrophils - Liu, Chunxiao; Zhou, Mengze; Jiang, Wenjiao; Ye, Shumin; Tian, Sheng; Jiang, Cheng; Hao, Kun; Li, Huanqiu; Hu, Qinghua (Frontiers in Immunology, 2022)
The fate of infiltrating neutrophils in inflamed joints determines the development of acute gouty arthritis (AGA). GPR105 highly expressed in human neutrophils is sensitive to monosodium urate crystals (MSU), nevertheless, roles of GPR105 in AGA remain unclear. Here we show that GPR105 is significantly up-regulated in peripheral polymorphonuclear neutrophils of AGA patients. GPR105 knockout (GPR105-/-) prevented against NETosis and induced apoptosis of neutrophils under MSU exposure, as well as attenuated inflammatory cascades in AGA. Mechanistically, GPR105 deletion activated cAMP-PKA signals, thereby disrupted Raf-Mek1/2-Erk1/2 pathway-mediated NADPH oxidase activation, contributing to inhibition of NETosis. Whereas, cAMP-PKA activation resulted from GPR105 deficiency modulated PI3K-Akt pathway to regulate apoptosis. More importantly, suppression of cAMP-PKA pathway by SQ22536 and H-89 restored NETosis instead of apoptosis in GPR105-/- neutrophils, promoting MSU-induced gout flares. Interestingly, lobetyolin was screened out as a potent GPR105 antagonist using molecular docking-based virtual screening and in vitro activity test, which efficiently attenuated MSU-induced inflammatory response interacting with GPR105. Taken together, our study implicated that modulating cell death patterns between NETosis and apoptosis through targeting GPR105 could be a potential therapeutic strategy for treatment of AGA.